Pengaruh Metode Cooperative Type Jigsaw Terhadap Peningkatan Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam di Kelas V MI Muhammadiyah 09 Kranji Lamongan - M. Chotibuddin (Jurnal Pendidikan Islam, 2021)
Learning and teaching are the most important activities in the whole educational process. This implies that the success or failure of the educational goals depends on how to design the teaching and learning process (learning) professionally. The success of the learning process cannot be separated from the preparation of students and the preparation of educators. In learning activities, methods are needed for educators and their use varies according to the goals to be achieved after teaching ends. An educator will not be able to carry out his duties if he does not master any of the teaching methods that have been formulated. The methods used in data collection are the observation method and the test method. The data analysis used was the instrument validity test, the normality test and the homogeneity test. The results of the research carried out proved that student learning outcomes before and after using the jigsaw method could be seen from the average pre-test scores of 62.00 and 76.60 post-test results. The pre-test result value is lower than the post-test score, so it means that there are differences in student learning outcomes before and after using the jigsaw method in the learning process.The percentage of the completeness criteria of the pre-test result value is 28%, while the posttest result score is 68%. From this data, it can be seen that using the jigsaw method can affect student learning outcomes. Hypothesis testing using the Product Moment Correlation test and Paired Sample T-test with the help of SPSS 20 software in the sig (2-tailed) section is known to be 0.000 <0.05. As the basis for decision making in the Product Moment Correlation test anddecision guidelines based on the probability value, it can be concluded that H0 is rejected and Ha is accepted. This means that the jigsaw method can affect the improvement of learning outcomes of class V Islamic Religious Education at MI Muhammadiyah 09 Kranji Lamongan